2009
DOI: 10.1007/s00394-009-0038-6
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products strongly activate platelets

Abstract: The increase in surface activation marker and RAGE expression in platelets, resulting from concentrations of AGEs that occur in vivo after a meal or a drink as a source of exogenous AGEs, points to signaling mechanisms for food AGEs that could favor the precipitation of acute postprandial ischemic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 31 publications
1
33
0
2
Order By: Relevance
“…However, though the effects of high levels of total plasma NEFAs have been studied (10,11,61), the putative deterioration in the NEFA binding capacity of albumin was not addressed in a systematic way. In previous studies, it was reported that oxidative stress and glycation caused conformational changes in albumin structure (14,29,62) with possible effects in vitro on platelet function (17,63,64). The novelty of the current study is the demonstration that glycation probably impairs the binding properties of albumin of patients with T2D.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, though the effects of high levels of total plasma NEFAs have been studied (10,11,61), the putative deterioration in the NEFA binding capacity of albumin was not addressed in a systematic way. In previous studies, it was reported that oxidative stress and glycation caused conformational changes in albumin structure (14,29,62) with possible effects in vitro on platelet function (17,63,64). The novelty of the current study is the demonstration that glycation probably impairs the binding properties of albumin of patients with T2D.…”
Section: Discussionmentioning
confidence: 75%
“…The nonenzymatic covalent attachment of glucose molecules to protein and the subsequent free radical-mediated oxidation give rise to advanced glycoxidation end (AGE) products, of which methylglyoxal (MGO) is considered a key component through the Amadori rearrangement (15). Several reports indicate that AGE products are able at least in vitro to induce activation of various cells including platelets (16,17). In addition to classical glycemic indices, several recent reports indicated that glycated albumin is a relevant and practical biomarker for the progression of diabetic atherosclerosis (18)(19)(20).…”
mentioning
confidence: 99%
“…Extracellular MRP-8/14 is then able to bind to receptors on target cells, including CD36 (8), RAGE (10), TLR4 (9), special carboxylated N-glycans (43), and heparin-like glycoaminoglycans (44). Interestingly, both CD36 (22) and RAGE (23) signaling have been directly implicated in platelet activation and thrombosis. Platelets also express functional levels of TLR4 (24), which may contribute to thrombocytopenia through neutrophil-dependent pulmonary sequestration in response to LPS (45).…”
Section: Discussionmentioning
confidence: 99%
“…Putative receptors for MRP-8/14 on target cells include CD36 (8), RAGE (10), and TLR4 (9). Interestingly, both CD36 (22) and RAGE (23) signaling have been directly implicated in platelet activation and thrombosis. Platelets also express functional levels of toll-like…”
Section: Role Of Intracellular Versus Extracellular Mrp-8/14 In Thrommentioning
confidence: 99%
“…"Advanced glycation end products" (AGEs) induzieren eine leukozytäre Apoptose und eine Expression von Mac-1, die eine Plättchen-Leukozyten-Aggregation bewirken [40]. AGEs stimulieren die Expression von Rezeptoren für AGEs (RAGE) auf der Plättchenoberfläche [41].…”
Section: Plättchenaktivierung Bei Diabetes Mellitusunclassified